The impact of nano-infused phase change materials and blossom-shaped fins on thermal energy storage - Hassan Waqas; Mohib Hussain; Qasem M. Al-Mdallal; N. Ameer Ahammad; Ibrahim E. Elseesy (Case Studies in Thermal Engineering)
The widespread implementation of a latent heat storage system (LHSS) presents a viable solution to the energy imbalance and shortages. Phase Change Materials (PCMs) are key components owing to their remarkable energy storage capabilities. However, the low heat conductivity of phase change materials presents a considerable challenge to their practical use. This study presents the modelling and numerical simulation of a latent heat storage system (LHSS) using blossom-shaped fins (BSF) and nano-integrated phase change material (PCM). The study evaluates the efficacy of the tube heat exchanger by examining multiple physical characteristics, including the number of fins, height, and the interaction between fin pin and height, using ANSYS Fluent and the finite volume approach. The findings indicate that the charging time is reduced by 17% based on modifications in fin compactness and quantity. Additionally, the nano-integrated PCM significantly reduces the amount of time required for melting. The findings demonstrate in comparison to the conventional PCM with nano-mediated PCM, the melting time of nano-integrated PCM is shortened by 18.6%,13.6%,14.7%,12.7% and 16.3% for Case A-1, Case A-4, Case B-1, Case C-2, and Case D-1, incorporating blossom-shaped fins. The findings can have an impact on future studies aimed at improving PCMs energy storage capabilities and creating more efficient heat exchanger designs.